2000
DOI: 10.1152/ajpheart.2000.278.4.h1134
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous cardiac sympathetic innervation in heart failure after myocardial infarction of rats

Abstract: We examined cardiac neuronal function and beta-receptor with a dual-tracer method of [(131)I]meta-iodobenzylguanidine (MIBG) and [(125)I]iodocyanopindolol (ICYP) in rat heart failure after myocardial infarction (MI). In rats with MI, left ventricular (LV) systolic function decreased, and LV dimension and right ventricular (RV) mass increased gradually. MIBG accumulations of the noninfarcted LV (remote region) and RV decreased by 15% at 1 wk compared with sham-operated rats, and these accumulations were restore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
2

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 41 publications
(55 reference statements)
2
17
2
Order By: Relevance
“…Although the present study confirms peri-infarct hyperinnervation (Cao, et al, 2000a;Cao, et al, 2000b), other studies have reported reduced cardiac sympathetic innervation after infarction (Barber, et al, 1983;Igawa, et al, 2000;Li, et al, 2004). These differences may be related to the extent of infarction as larger infarcts can result in frank congestive heart failure, and this has been linked to cardiac NGF depletion and diminished sympathetic axon density (Kaye, et al, 2000;Qin, et al, 2002).…”
Section: Selectivity Of Post-infarct Hyperinnervationsupporting
confidence: 64%
“…Although the present study confirms peri-infarct hyperinnervation (Cao, et al, 2000a;Cao, et al, 2000b), other studies have reported reduced cardiac sympathetic innervation after infarction (Barber, et al, 1983;Igawa, et al, 2000;Li, et al, 2004). These differences may be related to the extent of infarction as larger infarcts can result in frank congestive heart failure, and this has been linked to cardiac NGF depletion and diminished sympathetic axon density (Kaye, et al, 2000;Qin, et al, 2002).…”
Section: Selectivity Of Post-infarct Hyperinnervationsupporting
confidence: 64%
“…Experimental animals: Male Wistar rats weighing 300-350 g were used for the induction of MI, that was produced by ligation of the left coronary artery under ether anesthesia as reported previously. 19) Briefly, the left coronary artery was ligated approximately 2-3 mm from its origin with a suture (6-0 silk). With this method, the 24-hour survival rate was 57% in the infarcted rats.…”
Section: Methodsmentioning
confidence: 99%
“…7 Briefly, under ether anesthesia, a left thoracotomy was performed to expose the heart. The left coronary artery was ligated 2-3 mm from its origin with a 5-0 Prolene suture (Ethicon Inc, Somerville, NJ, USA) for 30 min and then the ligature was released (non-PC group).…”
Section: Animal Studiesmentioning
confidence: 99%
“…7 Briefly, 3 days after the induction of myocardial ischemia, 1.85 MBq of 131 I-MIBG (radiochemical purity >98%, specific activity 7.4 GBq/mg, Daiichi Radioisotope Laboratory, Chiba, Japan) was injected via the external jugular vein under pentobarbital anesthesia (30 mg/kg, ip). The heart was removed 3 h later.…”
Section: Animal Studiesmentioning
confidence: 99%
See 1 more Smart Citation